Learning Technology Area Ethical Studies and Practices in Learning Technology - Kamal; Muh. Rapi; Muhammad Rusdi Rasyid; Muhammad Hamsah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The world of education and learning develops dynamically in line with technological advances. Educational technology is the study and ethical practice of facilitating learning and enhancing performance by creating, using and managing appropriate technological processes and resources. It takes more than reading, writing, and arithmetic skills to participate, survive, and succeed in the knowledge society in the great competition of the 21st century. The global community demands its citizens to have the 21st skills such as critical thinking, problem solving, communication, collaboration, creativity, and innovation. Moreover, to prepare for the ideal type of the 21st person, our education system must carry out learning practices under deductive and inductive logic. At least educational technology has a major contribution to facilitating the right learning process to optimize the development of students' basic skills for their own good. education and learning in accordance with the technological foundation. The purpose of this article is to provide study material on the technological foundations of education and learning. The method used in this qualitative research is literature study, in which information is collected through documentation through books, journals, articles and relevant juridical foundations. The technological foundation is the basis used as a reference for ethical theory and practice that involves people systematically supporting and solving various problems or improving quality in the education and learning process. The role of educational technology is basically an effort to improve the quality of education and learning from time to time and must be able to facilitate learning in various conditions encountered. The use of educational technology in general is to make it easier for students to access learning resources that are not limited by distance and time, so that learning can run effectively and efficiently and the quality of education will get better in the future. The conclusion from the presentation of the material includes educational technology which has a broad meaning which emphasizes the education system, while learning technology focuses on implementing learning in accordance with the conditions of students